2010
DOI: 10.1097/sla.0b013e3181f4e499
|View full text |Cite
|
Sign up to set email alerts
|

Acute Glucose Elevation Is Highly Predictive of Infection and Outcome in Critically Injured Trauma Patients

Abstract: AGE is a highly accurate predictor of infection and should stimulate clinicians to identify a new source of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…In this study, the occurrence of hyperglycemia during the inductive chemotherapy did not significantly affect the CR rate of children (compared with the euglycemia group, 86.8% vs 95%, P=0.134), while the prognosis of the hyperglycemia group was poorer, the 5-year overall survival rate was significantly lower than the euglycemia group (83.1±6.3% vs 94.2±2.9%, P=0.014), the 5 -year relapse-free rate was also significantly lower than the euglycemia group (64.1±8.9% vs 88.6±3.8%, P<0.001). Several studies of adults had shown that the hyperglycemia could predict the higher mortality, the mean fasting blood glucose >112.5 mg/dl could significantly increase the mortality of cancer patients (Bochicchio et al, 2010;Seshasai et al, 2011), and the appearance of hyperglycemia in the inductive chemotherapy of adult ALL patients exhibited the poor prognosis, compared with the euglycemic patients, the risks of the early recurrence and higher mortality were 1.57 times and 1.71 times, respectively, with shorter median CR (24 months vs 52 months, P=0.001) and median survival time (29 months vs 88 months, P<0.001) (Weiser et al, 2004). currently, there were three research institutions that reported the relationship of hyperglycemia during the inductive remission with the childhood ALL, while the results were different .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the occurrence of hyperglycemia during the inductive chemotherapy did not significantly affect the CR rate of children (compared with the euglycemia group, 86.8% vs 95%, P=0.134), while the prognosis of the hyperglycemia group was poorer, the 5-year overall survival rate was significantly lower than the euglycemia group (83.1±6.3% vs 94.2±2.9%, P=0.014), the 5 -year relapse-free rate was also significantly lower than the euglycemia group (64.1±8.9% vs 88.6±3.8%, P<0.001). Several studies of adults had shown that the hyperglycemia could predict the higher mortality, the mean fasting blood glucose >112.5 mg/dl could significantly increase the mortality of cancer patients (Bochicchio et al, 2010;Seshasai et al, 2011), and the appearance of hyperglycemia in the inductive chemotherapy of adult ALL patients exhibited the poor prognosis, compared with the euglycemic patients, the risks of the early recurrence and higher mortality were 1.57 times and 1.71 times, respectively, with shorter median CR (24 months vs 52 months, P=0.001) and median survival time (29 months vs 88 months, P<0.001) (Weiser et al, 2004). currently, there were three research institutions that reported the relationship of hyperglycemia during the inductive remission with the childhood ALL, while the results were different .…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with greater in-hospital mortality, longer hospital stays, and increased rates of admission to the ICU. Additionally, the general trauma and critical care literature is replete with investigations on the relationship of hyperglycemia with morbidity and mortality following critical illness [9][10][11][12]15,16 , with some authors suggesting that ongoing persistent hyperglycemia and subsequent glucose control are predictive of outcome 21,24 . However, this has not been easily translated into results that may be applied in an environment outside of an ICU.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, early posttrauma hyperglycemia has been found to be a more reliable predictor of poor outcomes and mortality compared with later increases in plasma glucose (7,16). Hyperglycemia has been shown to increase ROS and affect neutrophil responses, including neutrophil retention (27) and exacerbated free radical release (28), which are important processes in innate immune responses (22,49) and ALI.…”
Section: Significance and Clinical Relevancementioning
confidence: 99%
“…Several clinical studies have suggested that, in critically ill obese patients, impaired glucose homeostasis appears to be a better predictor of increased complications and mortality than body mass index (38,41,45). In addition, there is evidence that the early hyperglycemia within the first day after trauma is a more reliable predictor of poor outcomes and mortality compared with later increases in plasma glucose (7,16). A study (45) monitoring glucose levels for 4 days after trauma showed that nonsurvivors only exhibited a significant increase in glucose (Ͼ150 mg/dl) within the first half day after trauma, with peak levels observed at admission.…”
mentioning
confidence: 98%
See 1 more Smart Citation